Ipsilateral Ophthalmic Artery Stenosis in Amaurosis Fugax: A Case Report - Referano Agustiawan; Ferdy Iskandar; Muhammad Ikhsan Mokoagow; Kanisius Kanovnegara; Firman Hendrik (International Journal of Retina, 2021)
Introduction: Amaurosis fugax is caused by an abrupt reduction of blood flow to the retina. Determining the etiology of amaurosis fugax should ensure proper management. Case Report: A 47-year-old female patient who had the first episode of amaurosis fugax in her right eye was referred to our hospital. The amaurosis fugax resolved spontaneously, however, we found a 3 mm long stenosis at her right ophthalmic artery during magnetic resonance angiography. She had clinical histories of untreated hypertension and dyslipidemia. Transient ischemic attack (TIA) was suspected and unfractionated heparin, aspirin, antihypertensive agent, and statin were given. Treatments were maintained, the symptoms had not recurred in the following 6 months after the event. Discussion: Stenosis of the ophthalmic artery is very rare. It occurs in approximately 2% of patient suffering from amaurosis fugax. In our case, stenosis of the right ophthalmic artery due to thromboembolism might cause retinal ischemia leading to a transient visual loss. Conclusion: This case suggests stenosis of ophthalmic artery as the cause of amaurosis fugax. Keywords: amaurosis fugax, ipsilateral, ophthalmic artery, stenosis